Suitable wheat cultivars and seeding machines for conservation agriculture in rice-wheat and sugarcane-wheat cropping systems - Chhokar, Rajender Singh; Sharma, Ramesh Kumar; Gill, Subhash Chander; Singh, R K; Joon, Vikas; Kajla, Mamta; Chaudhary, Ankur (Journal of Cereal Research, 2018)
Field investigations were conducted to improve the wheat yield through identification of suitable wheat cultivars and seeding machines after rice and sugarcane harvest. For wheat seeding under conservation agriculture (CA) after rice with full residue retention, Turbo Happy Seeder (THS) was more appropriate and in sugarcane ratoon with full trash, Rotary Disc Drill (RDD) was found suitable. Based on the research farm experiments and farmerâ€™s field demonstrations, the wheat grain yield was similar under Conventional tillage (CT) and CA. Among 32 wheat varieties evaluated under timely sown conditions, no significant yield differences were observed under CT and CA. Among test cultivars, the best yielding were HD 2967, PBW 723, HDCSW 18, HI 8498, MPO 1215, UAS 428, MACS 6222. For very late sown (20-25th January)and CA conditions after sugarcane harvest, five wheat varieties namely PBW 550, DBW 71, Raj 3765, WR 544 and WB 02 yielded 30.24, 33.80, 32.62, 32.46 and 27.54q/ha, respectively. On an average, 33 q/ha additional wheat yield can be obtained when seeded in sugarcane ratoon using RDD. If we translate 50% sugarcane area across the wheat growing zone of India (1 mha) then we can have an additional wheat production of 3.3 m t/year. Both the crop establishment methods viz. no till (NT) with residue retention and conventional till (CT) wheat had similar yield levels but CA can have an additional profit of Rs 3125/ha due to reduction on tillage cost. The results clearly indicate that wheat productivity and production as well as profitability can be improved through right choice of cultivar, and machinery for conservation agriculture in rice-wheat and sugarcane ratoon- wheat system. Â DOI:10.25174/2249-4065/2018/80127